Rare complications of sinusitis: case series - Tanthry, Deepalakshmi; Sunny, Chikku T.; Mahesh, S. G.; Devan, P. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Sinusitis complications affecting multiple sites are very uncommon in the antibiotic era. However, a significant proportion of patients (5-40%) suffering from acute sinusitis can have these complications mostly due to the delayed diagnosis of the disease. Patients can have variable presentations according to the site and extent of the infection. All the patients were subjected to thorough clinical examination, ophthalmological evaluation and radiological evaluation. Computed tomography of paranasal sinuses both axial and coronal planes, MRI in selected cases and histopathology are the study tools used in this study. All the patients in this study received appropriate medical and surgical treatment and done a follow up evaluation every month. A thorough clinical and radiological evaluation along with early management of the disease can prevent complications of sinusitis and further deterioration of the disease to a larger extent.